Influence Of Brand Personality On Brand Equity For Internet Service Provider (ISP\'S) In Malaysia - Boroujeni, Sina Borjian (2011)
The Internet service providers (ISPs) play a vital role in the ICT industries in any country and specifically, provide a crucial role in the economical prosperity of Malaysia. Strong brand personality definitely is a critical factor to enhance customer based brand equity of ISPs that help them not only to have a better influence on the customers inside Malaysia but to prepare Malaysian ISPs to compete with the international markets as well.